PEMIDANAAN PEMAKSAAN PERKAWINAN: PERSPEKTIF HUKUM POSITIF DAN MAQASHID AL-SYARIAH - Adhisvy Intania; Ahmad Fazlur Rahman; Nawala Shihabi Pramudya Imron; Kutbuddin Aibak (Maqasid: Jurnal Studi Hukum Islam, 2026)
Forced marriage is a form of human rights violation that threatens individual freedom and dignity, particularly for women. This phenomenon not only has social and psychological impacts on victims but also raises legal and ethical issues regarding the protection of personal dignity and an individual’s right to choose a life partner. This article aims to analyze the criminalization of forced marriage from the perspectives of positive law and maqashid al-shariah. This study employs a legal-normative method with a legislative and conceptual approach through a literature review. The novelty of this research lies in the effort to integrate criminal sanctions under the Law on Sexual Violence Crimes (UU TPKS) with the framework of the five fundamental principles of maqashid al-shariah, specifically regarding the issue of forced marriage, a perspective that has yet to be deeply explored in studies of Islamic family law in Indonesia. The findings indicate that forced marriage contradicts the objectives of both law and Sharia because it eliminates the element of consent (ridha) and causes harm to the victim. Therefore, criminalizing the perpetrator is viewed as a normative measure that supports the protection of life (hifz al-nafs), honor (hifz al-’irdh), and lineage (hifz al-nasl). Implicitly, this study provides a theoretical foundation for strengthening regulations on the protection of women and can serve as a reference for legal practitioners and academics in reinforcing religious-normative arguments regarding the implementation of the TPKS Law in society.   Keywords: Criminalization, Forced Marriage, Positive Law, and Maqasid al-Shariah.